Design of a highly sensitive blood sensor based on a 2D photonic crystal L3 cavity - Sharma, Puja; Medhekar, Sarang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
In this paper, a 2D photonic crystal (PC) biosensor is proposed. The basic PC structure consists of 17 × 15 holes in X and Z direction over a silicon slab of refractive index (RI) equal to 3.46. The sensor structure consists of two L3 cavities created on the either side of a defect waveguide. The band diagram of the proposed structure is analyzed using plane wave expansion method (PWEM) and simulations of light propagation through the biosensor are carried out using 2D finite difference time domain method (2D-FDTDM). The parameters are optimized to obtain the best possible performance. The sensitivity of the proposed biosensor is determined by the shift in the wavelength of transmission deep as a function of RI of sensing holes. The proposed biosensor exhibits a high-quality factor (Q-factor) of 2587, with a spectral width of 0.6 nm (at the wavelength of 1552 nm) of the transmission deep. The biosensor has ultra-compact footprint of 29 µm2. Further, it shows a high figure of merit (666 RIU–1), a low detection limit (1.49 × 10–4 RIU), and a maximum sensitivity of 400 nm/RIU. The proposed biosensor might have potential applications in detection of many blood related diseases.
Optica Applicata, Vol. 55, 2025, nr 2, s. 157-168
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; photonic crystal; photonic bandgap; PBG; L3 cavity; plane wave expansion method; PWEM; finite difference time domain method; FDTDM